A phase II study to evaluate the safety and efficacy of topical 3% amphotericin B cream (Anfoleish) for the treatment of uncomplicated cutaneous leishmaniasis in Colombia (2018)
ABSTRACT: Pentavalent antimonials (Sb5) are the first-line drugs for treating cutaneous leishmaniasis in Colombia; however, given problems with toxicity, compliance, availability, and cost, it is imperative to look for better therapeutic options. Intravenous amphotericin B (AmB) has been used extensively to treat visceral leishmaniasis; however, evidence on its topical use for cutaneous leishmaniasis is limited. Anfoleish is a topical formulation based on 3% AmB, which was developed following GMP standards by HUMAX and PECET. Anfoleish was shown to be safe and efficacious in animal model and in an open label study in CL patients. Hereafter we show the results of the first controlled and randomized study assessing the safety and efficacy of Anfoleish administered topically, two or three times per day for 28 days, for the treatment of non-complicated cutaneous leishmaniasis in Colombia.